The influence of work team and work environment on the character of loyalty to the organization (Study at the Hikmah Masamba General Hospital) - Chaerani Bintang; Muhammad Kasran; Suparni Sampetan (Global Academy of Multidisciplinary Studies, 2024)
Purpose: This study aimed to determine the influence of work teams and work environments on the character of loyalty to the organization, focusing on employees of Hikmah Masamba General Hospital. Research Methodology: The research employed a descriptive quantitative approach with a total population of 50 employees, consisting of 26 from HR nursing services and 24 from HR midwifery services. Using a saturated sampling technique, all members of the population were included as the respondents. Data were analyzed using SPSS 26, enabling partial and simultaneous testing of the relationships between variables. Results: The findings show that both the work team and work environment exert a significant influence, individually and collectively, on the development of organizational loyalty among employees. This indicates that supportive teamwork and a conducive work environment are essential factors for strengthening loyalty within healthcare institutions. Conclusions: The study concludes that employee loyalty is significantly shaped by the quality of teamwork and the conditions of the work environment. Improving these two factors can enhance organizational commitment and sustainability in the management of hospitals. Limitations: The main limitation of this study is that data were collected from only one institution, limiting the generalizability of the findings to broader contexts. Contribution: This study is expected to serve as a reference for future research exploring loyalty characteristics in healthcare and other organizational contexts.